The Role of Humor in Startup Success: The Mediating Role of Team Performance (Journal of Organizational Psychology, 2017)
Entrepreneurial ventures have high rates of failure in converting an idea to a business. We seek to understand the role of humor to sustain ventures. Research shows us that humor plays a critical role in team performance. A strong team can overcome the initial hiccups of a startup and increase the chances of success. This study benchmarks the level of humor, then does an intervention of a “humor training session,” and measures its effects. We theorize that there will be an increase in team performance due to stress reduction, which will lead to a likelihood of survival of the startup.
Keywords: Organizational Psychology; Entrepreneurship; Humor